Association of specific pectin methylesterases with Al‐induced root elongation inhibition in rice. Issue 4 (12th December 2012) - Yang, Xiao Ying; Zeng, Zhang Hui; Yan, Jing Ying; Fan, Wei; Bian, Hong Wu; Zhu, Mu Yuan; Yang, Jian Li; Zheng, Shao Jian
Abstract : The negative charges of cell wall pectin molecules attributed by pectin methylesterase (PME, EC 3.1.1.11) contribute to Al binding capacity. We examined the expression profiles of 35 members of the PME gene family in the root apex of an Al‐sensitive rice 'Zhefu802' under Al stress. While root elongation was inhibited by 40% after 3‐h exposure to 25 µ M Al, cell wall PME activity and the abundance of eight PME genes transcripts were increased. The same Al treatment which had almost no effect on root elongation of an Al‐resistant rice ssp. japonica 'Nipponbare' did not change the expression patterns of these eight PME genes. However, when Al concentration was increased to 50 µ M, by which the root elongation of 'Nipponbare' was inhibited by 40% too, the expression of these PME genes were also upregulated except two genes with no signal. These suggest a possible correlation between the upregulated genes and Al‐induced inhibition of root elongation in rice. Furthermore, these eight PME genes behaved differently when subjected to CdCl2 and LaCl3 treatments, implying the specificity of different PME genes in response to different metal toxicities. The transgenic rice overexpressing one of these eight PME genes OsPME14 showed higher PME activity and Al content in root tip cell wall, and became more sensitive to Al stress, verifying the involvement of the specific PME gene in Al toxicity. Therefore, our results provided the molecular evidence to connect the expression of specific PME genes with the Al‐induced inhibition of root elongation in rice.